Rodzina jako podmiot przedsiębiorczy – krytyczna analiza dyskursu wychowania małego geniusza w portalach internetowych dla rodziców. - Popow, Monika (Kultura-Społeczeństwo-Edukacja, 2014)
The aim of this paper is to analyse the infant prodigy discourse in popular Polish internet portals for parents. As a result of Critical Discourse Analysis, key rhetoric strategies, constructing the representation of a child and its family, have been identified. Subsequently, the analysis of particular discursive strategies, including professionalization of parenthood and discursive construction of a family as an entrepreneur of the self, have been conducted.